Temporal Trends in the Incidence and Natural History of Diverticulitis: A Population‐Based Study. (November 2015) - Bharucha, Adil E; Parthasarathy, Gopanandan; Ditah, Ivo; Fletcher, J G; Ewelukwa, Ofor; Pendlimari, Rajesh; Yawn, Barbara P; Melton, Joseph L; Schleck, Cathy; Zinsmeister, Alan R
Abstract : OBJECTIVES: Data on the incidence and natural history of diverticulitis are largely hospital‐based and exclude the majority of diverticulitis patients, who are treated in an outpatient setting for uncomplicated diverticulitis. We assessed temporal trends in the epidemiology of diverticulitis in the general population. METHODS: Through the Rochester Epidemiology Project we reviewed the records of all individuals with a diagnosis of diverticulitis from 1980 to 2007 in Olmsted County, Minnesota, USA. RESULTS: In 1980–1989, the incidence of diverticulitis was 115/100, 000 person‐years, which increased to 188/100, 000 in 2000–2007 ( P <0.001). Incidence increased with age ( P <0.001); however, the temporal increase was greater in younger people ( P <0.001). Ten years after the index and second diverticulitis episodes, 22% and 55% had a recurrence, respectively. This recurrence rate was greater in younger people (hazard ratio (HR) per decade 0.63; 95% confidence interval (CI), 0.59–0.66) and women (HR 0.68; 95% CI, 0.58–0.80). Complications were seen in 12%; this rate did not change over time. Recurrent diverticulitis was associated with a decreased risk of complications ( P <0.001). Age was associated with increased risk of local (odds ratio (OR) 1.27 per decade; 95% CI, 1.04–1.57) and systemic (OR 1.83; 95% CI, 1.20–2.80) complications. Survival after diverticulitis was lower in older people ( P <0.001) and men ( P <0.001) and worsened over time ( P <0.001). The incidence of surgery for diverticulitis did not change from 1980 to 2007. CONCLUSIONS: The incidence of diverticulitis has increased by 50% in 2000–2007 compared with 1990–1999, and more so in younger people. Complications are relatively uncommon. Recurrent diverticulitis is frequent but typically uncomplicated. Younger people with diverticulitis have less severe disease, more recurrence, and better survival.